Paradoxical proepileptic response to NMDA receptor blockade linked to cortical interneuron defect in stargazer mice - Maheshwari, Atul; Nahm, Walter; Noebels, Jeffrey (Frontiers in Cellular Neuroscience, 2013)
Paradoxical seizure exacerbation by anti-epileptic medication is a well-known clinical phenomenon in epilepsy, but the cellular mechanisms remain unclear. One possibility is enhanced network disinhibition by unintended suppression of inhibitory interneurons. We investigated this hypothesis in the stargazer mouse model of absence epilepsy, which bears a mutation in stargazin, an AMPA receptor trafficking protein. If AMPA signaling onto inhibitory GABAergic neurons is impaired, their activation by glutamate depends critically upon NMDA receptors. Indeed, we find that stargazer seizures are exacerbated by NMDA receptor blockade with CPP (3-[(R)-2-carboxypiperazin-4-yl]-prop-2-enyl-1-phosphonic acid) and MK-801, whereas other genetic absence epilepsy models are sensitive to these antagonists. To determine how an AMPA receptor trafficking defect could lead to paradoxical network activation, we analyzed stargazin and AMPA receptor localization and found that stargazin is detected exclusively in parvalbumin-positive (PV +) fast-spiking interneurons in somatosensory cortex, where it is co-expressed with the AMPA receptor subunit GluA4. PV + cortical interneurons in stargazer show a near twofold decrease in the dendrite:soma GluA4 expression ratio compared to wild-type (WT) littermates. We explored the functional consequence of this trafficking defect on network excitability in neocortical slices. Both NMDA receptor antagonists suppressed 0 Mg 2+-induced network discharges in WT but augmented bursting in stargazer cortex. Interneurons mediate this paradoxical response, since the difference between genotypes was masked by GABA receptor blockade. Our findings provide a cellular locus for AMPA receptor-dependent signaling defects in stargazer cortex and define an interneuron-dependent mechanism for paradoxical seizure exacerbation in absence epilepsy.